Prevalência de Helicobacter pylori em endoscopia digestiva alta pediátrica - Kohl, Letícia Signori (2018)
Introduction: Helicobacter pylori infection in the gastric mucosa in children causes several changes and differs from the manifestations of infection in adults. However, it should be investigated in pediatric patients, even without manifestations. Objective: to determine the prevalence of Helicobacter pylori infection in children aged zero to 12 years old submitted to High Digestive Endoscopy at Hospital São Vicente de Paulo from 2010 to 2017, correlating the endoscopic and anatomopathological findings. Methods: A descriptive and descriptive crosssectional study was carried out. The files of the upper digestive endoscopy (EDA) system and anatomopathological reports were analyzed. Results: A total of 407 patients were analyzed and a prevalence of 6.4% was obtained (95% CI: 4-9). In the EDA, 65.4% of the patients infected with HP did not present alterations in the gastric mucosa. In the anatomopathological analysis, all the infected patients had alterations in the stomach, being more prevalent the moderate chronic gastritis in the antrum. Conclusion: The study has showed a significant relationship between Helicobacter pylori infection and anatomopathological changes even with endoscopically normal EDA.